2012
DOI: 10.1080/08897077.2011.639696
|View full text |Cite
|
Sign up to set email alerts
|

Reinventing the Reel: An Innovative Approach to Resident Skill-Building in Motivational Interviewing for Brief Intervention

Abstract: To enhance the skills of primary care residents in addressing substance misuse, residency screening, brief intervention, and referral to treatment (SBIRT) programs increasingly offer motivational interviewing (MI) training, but seldom include feedback and coaching. This innovative 2-round "Virginia Reel" approach, supplementing 3 hours of basic MI instruction, was designed to teach and coach residents to use MI while providing ongoing medical care. SBIRT/MI-competent facilitators served as both trainers and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 6 publications
2
42
0
1
Order By: Relevance
“…A few studies reported a discrete intervention, such as a single workshop, 18,22,23 whereas others described more intensive MI interventions, including multiple sessions within a communication curriculum, 20 a dedicated MI rotation, 17 and a longitudinal MI curriculum. 16 Content of the interventions was mixed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A few studies reported a discrete intervention, such as a single workshop, 18,22,23 whereas others described more intensive MI interventions, including multiple sessions within a communication curriculum, 20 a dedicated MI rotation, 17 and a longitudinal MI curriculum. 16 Content of the interventions was mixed.…”
Section: Resultsmentioning
confidence: 99%
“…Most interventions used skills practice with feedback via resident role play, standardized patient exercises, direct observation in clinic, and objective structured clinical examination (OSCE). 16,17,[19][20][21][22][23][24] Three studies observed residents engaging in MI during actual patient encounters. 16,17,24 Assessment and outcomes varied across studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations